Changes in Oral Mucosa during Pregnancy (Indian Journal of Public Health Research & Development, 2020)
The main aim of this review is to understand the changes in oral mucosa during pregnancy. This reviewhighlights the major oral complication during pregnancy. Changes in the gingiva and physiologicalstructure of the tooth take place in addition to hormonal, immunologic, dietary and behavioural changes.Characteristics of pregnancy gingivitis are that it gets swollen, smooth and tends to bleed easily. Enlargementof gingiva may occur but it tends to resolves within few months after delivery. Due to the increase in salivarymicroorganisms, there may be a decrease in salivary pH and impairment of buffer effect. This may also leadto dental caries or erosion during lactation period.The dental management of pregnant patients requires special attention. Dentists, for example, may delaycertain elective procedures so that they coincide with the periods of pregnancy which are devoted tomaturation versus organogenesis. At other times, the dental care professionals need to alter their normalpharmacological armamentarium to address the patients’ needs versus the foetal demands. Applying thebasics of preventive dentistry at the primary level will broaden the scope of the prenatal care. Dentistsshould encourage all the patients of the childbearing ages to seek oral health counselling and examinationsas soon as they learn that they are pregnant
Keywords: Pregnancy, Oral mucosa, Gingivitis, Oral Cavity, Pregnancy Granuloma